2020
DOI: 10.1177/0300060520914826
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum pepsinogen I, pepsinogen II, and gastrin-17 levels for population-based screening for early-stage gastric cancer

Abstract: Objective: Diagnosing gastric cancer (GC) at early stages is important for reducing its mortality. This study evaluated the diagnostic value of serum pepsinogen (PG) I, PGII, and gastrin-17 (G17) levels in screening for early-stage GC. Methods: Serum levels of PGI, PGII, and G17 were measured in patients with upper digestive tract symptoms or GC family histories, and the PGI to PGII ratio (PGR) was calculated. Receiver operator characteristic curves were used to determine the thresholds of PGI, PGR, and G17 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
2
14
0
Order By: Relevance
“…PG is almost exclusively secreted by the stomach, and the secretion amount will also change during the secretion stage. Therefore, PG subgroups can reflect the changes in the number of gastric mucosal glands and cells, as well as the secretory function of different mucosal sites (15,16). When the gastric mucosa is atrophic, the number of gastric corpus glands and fundus glands decrease due to the replacement of the pyloric glands, followed by the decrease of principal cells.…”
Section: Discussionmentioning
confidence: 99%
“…PG is almost exclusively secreted by the stomach, and the secretion amount will also change during the secretion stage. Therefore, PG subgroups can reflect the changes in the number of gastric mucosal glands and cells, as well as the secretory function of different mucosal sites (15,16). When the gastric mucosa is atrophic, the number of gastric corpus glands and fundus glands decrease due to the replacement of the pyloric glands, followed by the decrease of principal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the value of gastrin in the diagnosis of GC, Tu et al and Wang et al conducted cohort studies using the method of epidemiology survey. 17 , 18 Although they got the data of diagnostic accuracy, the reliability is relatively low because of the method and very few GC patients. 17 , 18 In our studies, we found that the positive rate of gastrin-17 was 22.61% in GC, but the sensitivity of gastrin-17 could reach to 71.30% (95% CI: 65.00–77.10%) for diagnosing GC after using an optimal cutoff value.…”
Section: Discussionmentioning
confidence: 99%
“…15 , 16 Although Tu et al and Wang et al evaluated the diagnostic value of gastrin-17 for GC, they mainly aimed to assess the association between gastrin-17 and GC by using the method of epidemiology survey, not a diagnostic test. 17 , 18 Therefore, the effect of gastrin in the diagnosis of GC should be clarified further.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrin is a gastrointestinal hormone secreted by gastric antrum G cells, and its level is mainly affected by the number and function of G cells, as well as by the negative feedback regulation of gastric acid [7] . As a gastrointestinal hormone, G17 can not only maintain the integrity of digestive tract structure, but also regulate the function of digestive tract.…”
Section: Discussionmentioning
confidence: 99%